Determinants of reinvestment allowance utilization, effective tax rate and performance among incentivized company: the moderating effects of company’s directorship / Fairus Halizam A. Hamzah - A. Hamzah, Fairus Halizam (2021)
The implementation of tax incentives has always been regarded as controversial as it is vulnerable to misuse. Tax incentives are also prone to be subjected to several possible pitfalls that can be costly to a country's economy. In Malaysia, the government has introduced various tax incentives to corporate taxpayers, where the most prominent tax incentives type is known as the Reinvestment Allowance (RA). The RA is an incentive offered to a company in the manufacturing industry to stimulate capital reinvestment and encourage business expansion which ultimately reduces the cost of doing business through tax deductions. However, the Bank Negara Malaysia addressed its concerns about the effectiveness of these tax incentives in accomplishing the desired outcomes. Previous studies demonstrated that RA plays a role in encouraging investment among large corporations in Malaysia. Despite this, the empirical evidence available only provides limited information about RA’s utilization rate, its effectiveness in stimulating performance, and its possible use as a tax planning mechanism. The current study sought to examine the determinants of RA utilization among corporate taxpayers in Malaysia. The regression analyses were carried out on the data extracted from the administrative tax return and internally generated Case Management System of the Inland Revenue Board of Malaysia. The results show that the internal factors; profitability, effective tax planning, company's distinctive profile and director’s role and the external factor; the tax monitoring demonstrate the company’s success in fully utilizing RA. The time trend analysis proves that incentivized companies could maintain low effective tax rates over ten years due to RA utilization's tax planning opportunity. The third findings show that the RA utilization, the effective tax planning, the book-tax gap, company profiling, and tax monitoring are associated with company performance, indicating that its success depends on RA and heavily reliant on other tax attributes to succeed. The RA utilization in companies was also found to be an effective measure in enhancing the company's economic performance but is less effective in encouraging the company's business expansion. In strengthening RA's effectiveness, governments are urged to implement robust performance-based specifications to optimize tax incentive economic gains. Finally, the results show that the director's role as an internal governance moderates RA utilization and effective tax planning to enhance the company’s performance. These significant findings provide in-depth insights into the utilization and exploitation of RA among corporate taxpayers in Malaysia. This study's findings also validate the RA's applicability and relevance in contributing to the firm growth theory, tax planning theory, and agency theory.